2020
DOI: 10.3847/2041-8213/abb19c
|View full text |Cite
|
Sign up to set email alerts
|

Electron Heating in Perpendicular Low-beta Shocks

Abstract: Collisionless shocks heat electrons in the solar wind, interstellar blast waves, and hot gas permeating galaxy clusters. How much shock heating goes to electrons instead of ions, and what plasma physics controls electron heating? We simulate 2-D perpendicular shocks with a fully kinetic particle-in-cell code. For magnetosonic Mach number Mms ∼ 1-10 and plasma beta βp < ∼ 4, the post-shock electron/ion temperature ratio Te/Ti decreases from 1 to 0.1 with increasing Mms. In a representative Mms = 3.1, βp = 0.25 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Here we study electron heating processes at high-Machnumber shocks with  M 20 A . It was already reported that PIC simulations of low-Mach-number shocks (Tran & Sironi 2020) demonstrate good consistency of simulations and in situ measurements of Earth's (Schwartz et al 1988) and Saturn's (Masters et al 2011) bow shocks. The superadiabatic electron heating (above the limit predicted by the Rankine-Hugoniot condition) is associated with the cross-shock potential and interaction with ion-scale waves in the shock transition.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Here we study electron heating processes at high-Machnumber shocks with  M 20 A . It was already reported that PIC simulations of low-Mach-number shocks (Tran & Sironi 2020) demonstrate good consistency of simulations and in situ measurements of Earth's (Schwartz et al 1988) and Saturn's (Masters et al 2011) bow shocks. The superadiabatic electron heating (above the limit predicted by the Rankine-Hugoniot condition) is associated with the cross-shock potential and interaction with ion-scale waves in the shock transition.…”
Section: Introductionmentioning
confidence: 52%
“…In addition to accelerating particles, these processes cause some amount of electron heating; however, the relative contribution from each is yet to be determined. Electrons also can be heated via the shock potential that is widely discussed in the low-Mach-number regime (Thomsen et al 1987;Chen et al 2018;Tran & Sironi 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the fact that electrons are dynamically unimportant and can acquire energy from protons, as shown by particle-in-cell (PIC) simulations (see, e.g. Tran & Sironi 2020;Bohdan et al 2020). Now, if the electron injection into DSA were related to the same mechanism responsible for their heating, a direct consequence would be an electron injection efficiency inversely proportional to the shock speed.…”
Section: Results For Time Dependent Injectionmentioning
confidence: 99%
“…In the theory and simulations of this work, only a pair plasma was considered; this choice simplified the problem by ensuring that the downstream temperatures would be the same for both species. In shocks comprised of electron-proton plasmas, it is likely that the temperature of each species will be different (Tran & Sironi 2020). This added complexity should be further explored to insure the applicability of this work to space and astrophysical shocks and will be considered in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…This choice was motivated by two reasons: the temperature of the two species would have the same value downstream of the shock and the instabilities, relevant for this problem, are unchanged in the electron-positron limit (Gary & Karimabadi 2009;Schlickeiser 2010). In the ion-electron limit, the temperature of the two species is not necessarily equal (Guo et al 2017(Guo et al , 2018Tran & Sironi 2020), however, examining this problem in this framework would require a description of the ion/electron energy partition. While this is an important step in understanding the physics of non-relativistic collisionless shocks, it is beyond the scope of this work The setup of the shock simulations are similar to those described in Spitkovsky (2008b); Sironi & Spitkovsky (2011b); Sironi et al (2013), where the shock is formed by initializing the plasma with a supersonic flow towards a reflecting wall (in the negative 𝑥 direction) on the left hand side of the simulation.…”
Section: Simulationsmentioning
confidence: 99%